FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT INFLASI PROVINSI BALI - Adiyadnya, Made Santana Putra; Putra, Gde Bagus Brahma; Santosa, I Made Edy Septian (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2021)
Inflation is one indicator to maintain the level of stability of economic activities carried out by people in a country, including Indonesia. This very high inflation phenomenon can occur due to pressure arising from the supply side (cost push inflation), and from the demand side(demand pull inflation) as well as from the side of inflation expectations itself. The purpose of this study are 1) to know the effect of the exchange rate on the inflation rate in Bali Province; 2) to know the effect of export value on the inflation rate in Bali Province; 3) to know the effect of the money supply on the inflation rate in Bali Province. The analytical tool used is multiple linear regression analysis. The result of this research were : 1) exchange rate partially has no effect on the inflation rate in Bali Province; 2) export value partially has a negative and significant effect on the inflation rate in Bali Province; 3) money supply partially has a positive and significant effect on the inflation rate in Bali Province.